Klinický obraz a průbĕh aneurysmat aorty u osob vyssího vĕku - Weber, P; Cernák, P; Martínek, K; Hakl, L; André, I; Hrusovský, S; Dúbrava, M; Novotný, I (Casopis lekaru ceskych, 1989)
The authors discuss 11 patients with aortal aneurysms (AA) which they diagnosed in the course of 1983-1988. In seven instances the abdominal aorta was affected; once the ascending part and once the arch; twice the descending part and once the whole aorta. In four patients the aneurysm had a dissecting character. Patients of advanced age were involved (73.9 +/- 9.7 years) with multiple morbidity and frequently also general advanced atherosclerosis which was the main cause of development of aneurysms. The authors analyze the clinical picture and course of AA in different patients and draw attention to their great variability. In the discussion they deal with the position of diagnostic methods, analyze critically the causes, course and prognosis of AA incl. interpretation of their own group of patients. In view of the frequent (and rising) incidence of AA in old age, the authors consider it important to pay attention to this problem also from the aspect of clinical gerontology.
Keywords: Aged, 80 and over; aortální aneurysma; Male; senioři nad 80 let; Aged; lidé; Female; mužské pohlaví; ženské pohlaví; senioři; lidé středního věku; Humans; Aortic Aneurysm; Middle Aged